2010
DOI: 10.1007/s00213-010-2020-7
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of acute and chronic intermittent phencyclidine-induced performance deficits in the 5-choice serial reaction time task: influence of clozapine

Abstract: Acute NMDA receptor antagonism impairs inhibitory control, whereas repeated treatment produces delayed deficits in cognitive processing speed. The ability of clozapine partially to restore persistent PCP-induced deficits in processing speed and in lnBeta is consistent with clinical findings. This suggests that the enduring effects of repeated PCP treatment, combined with SDA, offers a useful, translational, approach to evaluate novel cognitive enhancers in the 5-CSRTT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…For example, chronic intermittent PCP in adult male rats (2.58 mg/kg; i.p. ; daily for 5 days and then 3 days per week for 3 weeks) produces a reduction in the speed of processing 24h but not 30 min post-treatment (Thomson et al, 2011). Similar results were observed in repeated PCP-treated rats (2 mg/kg; s.c.; 2 consecutive days, followed by a 2-week PCP-free period and then 5 consecutive days of PCP treatment, given 30-min before 5-CSRTT testing) (Amitai and Markou, 2009;Amitai et al, 2007).…”
Section: Speed Of Processingsupporting
confidence: 86%
“…For example, chronic intermittent PCP in adult male rats (2.58 mg/kg; i.p. ; daily for 5 days and then 3 days per week for 3 weeks) produces a reduction in the speed of processing 24h but not 30 min post-treatment (Thomson et al, 2011). Similar results were observed in repeated PCP-treated rats (2 mg/kg; s.c.; 2 consecutive days, followed by a 2-week PCP-free period and then 5 consecutive days of PCP treatment, given 30-min before 5-CSRTT testing) (Amitai and Markou, 2009;Amitai et al, 2007).…”
Section: Speed Of Processingsupporting
confidence: 86%
“…Indeed, several studies reported that NMDA antagonists (other than ketamine) increase impulsivity in the 5-CSRTT. That is the case of acute treatment with MK-801 or phencyclidine (Paine and Carlezon, 2009; Thomson et al, 2011; Barnes et al, 2012). Similarly, our group has shown that an acute challenge with MK-801 is able to increase all measures of impulsive behavior in the VDS (Leite-Almeida et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our group has shown that an acute challenge with MK-801 is able to increase all measures of impulsive behavior in the VDS (Leite-Almeida et al, 2013). On the other hand, chronic treatment may display a different behavioral pattern, either reduced PR during a 24-h drug withdrawal (Paine and Carlezon, 2009) or had no effect (Thomson et al, 2011; Barnes et al, 2012). Until now, most research seems to show a tendency of NMDA antagonists to increase impulsive behavior after an acute exposure, while on sub-chronic and chronic regimens the response seems to be towards a decrease in impulsive response particularly if the test is made during the withdrawn period.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol was according to our standard procedures (Thomson et al 2011). Mice were first habituated to the liquid reinforcer (Yazoo® Strawberry Milkshake) and operant boxes before undergoing 10 stages of training, which took 65 daily sessions in total.…”
Section: Methodsmentioning
confidence: 99%